y+4=-13⋅(x-3)

The slope-intercept form is y=mx+b, where m is the slope and b is the y-intercept.

y=mx+b

Simplify -13⋅(x-3).

Apply the distributive property.

y+4=-13x-13⋅-3

Combine x and 13.

y+4=-x3-13⋅-3

Cancel the common factor of 3.

Move the leading negative in -13 into the numerator.

y+4=-x3+-13⋅-3

Factor 3 out of -3.

y+4=-x3+-13⋅(3(-1))

Cancel the common factor.

y+4=-x3+-13⋅(3⋅-1)

Rewrite the expression.

y+4=-x3-1⋅-1

y+4=-x3-1⋅-1

Multiply -1 by -1.

y+4=-x3+1

y+4=-x3+1

Move all terms not containing y to the right side of the equation.

Subtract 4 from both sides of the equation.

y=-x3+1-4

Subtract 4 from 1.

y=-x3-3

y=-x3-3

Rewrite in slope-intercept form.

y=-13x-3

y=-13x-3

Using the slope-intercept form, the slope is -13.

m=-13

Find the Slope y+4=-1/3*(x-3)